Every breath you take - Clark, Mary Higgins; Burke, Alafair (2017)
Laurie Moran's professional life is a success. Her television show Under Suspicion is a hit, both in the ratings and its record of solving cold cases. But her romantic break from former host Alex Buckley has left her with on-air talent she can't stand -- Ryan Nichols -- and a sense of loneliness, despite her loving family. Now Ryan has suggested a new case. Three years ago, Virginia Wakeling, a member of the Board of Trustees of the Metropolitan Museum of Art, was found dead in the snow after being thrown from the museum's roof on the night of its most celebrated fundraiser, the Met Gala. The leading suspect then and now is her much younger boyfriend and personal trainer, Ivan Gray. Ivan runs a trendy, successful boutique gym called Punch -- a business funded in no small part by the late Virginia -- which happens to be the gym Ryan frequents. Laurie's skepticism about the case is upended by a tip from her father's NYPD connection, and soon Laurie realizes there are a bevy of suspects, including members of Virginia's trusted inner circle. As the Under Suspicion crew pries into the lives of a super wealthy real estate family with secrets to hide, danger mounts for several witnesses -- and for Laurie
Recreational Reading Collection
Keywords: Television programs -- Fiction; Television personalities -- Fiction; Missing persons -- Investigation -- Fiction; Rich people -- Crimes against -- Fiction; Dysfunctional families -- Fiction; Cold cases (Criminal investigation) -- Fiction; Reality television programs -- Fiction; Television personalities -- Fiction; Missing persons -- Investigation -- Fiction; Television programs -- Fiction; Cold cases (Criminal investigation) -- Fiction; Romantic suspense fiction; Suspense fiction; Mystery fiction; Thrillers (Fiction); Detective and mystery fiction